Using job changes to evaluate the bias of the value of a statistical life - Hannes Spengler; Sandra Schaffner (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper presents a new approach to obtain unbiased estimates of the value of a statistical life (VSL) with labor market data. Investigating job changes, we combine the advantages of recent panel studies, which allow to control for unobserved heterogeneity of workers, and conventional cross-sectional estimations, which primarily exploit the variation of wage and risk between different jobs. We find a VSL of 6.1 million euros from pooled cross-sectional estimation, 1.9 million euros from the static first-differences panel model and 3.5 million euros from the job-changer specification. Thus, ignoring individual heterogeneity causes overestimates of the VSL, whereas identifying the wage-risk tradeoff not only by means of between job variation (job-changer model) but also on the basis of noisy variation on the job (panel models) may lead to underestimates of the VSL. Our results can be used to perform cost-benefit analyses of public projects aimed at reducing fatality risks, e.g., in the domains of health, environmental or traffic policy.
Keywords: I10; J17; J28; K00; 330; Value of a statistical life (VSL); compensating wage differentials; work accidents; job changes; Mensch; Bewertung; Wert des Lebens; Bias; Arbeitsmobilität; Theorie